In Situ X‐ray Absorption Fine Structure Spectroscopy of a Palladium Catalyst for the Direct Synthesis of Hydrogen Peroxide: Leaching and Reduction of the Metal Phase in the Presence of Bromide Ions. Issue 22 (4th September 2015) - Centomo, Paolo; Meneghini, Carlo; Sterchele, Stefano; Trapananti, Angela; Aquilanti, Giuliana; Zecca, Marco
Abstract: For the first time a Pd catalyst for the direct synthesis (DS) of H2 O2 from H2 and O2 was investigated using in situ Pd K‐edge X‐ray absorption fine structure spectroscopy. The catalyst was loaded into a continuous reaction cell and fed at room temperature and pressure with a mixture of CO2, O2, H2 (86:10:4, v/v), and methanol. Pd and PdO phases are observed in similar and steady proportions (62 and 28 %, respectively). The same is found if the catalyst is either dry or treated with pure methanol only. With 10 ppm of NaBr in the reaction mixture both the Pd edge jump and the fraction of PdO decrease steadily during the DS. This shows that Br − ions promote both the leaching and the reduction of Pd in a monometallic DS catalyst. It also suggests that they are connected to each other and to the ability of Br − ions to promote Pd in the DS. An unprecedented mechanism of protection and remediation supported by Br − ions against the overoxidation of Pd is proposed and discussed in this context. Abstract : X‐Rated : In situ X‐ray absorption fine structure spectroscopy of a Pd catalyst for the direct synthesis of hydrogen peroxide highlights the assistance of Br − ions to remove oxidized Pd from the surface through a dynamic leaching action.